Characterization and Determination of Critical Interlaminar Fracture Toughness of Carbon- Epoxy with Arcan Specimen - Masoud Nikbakht; Naghdali Choupani (International Journal of Advanced Design and Manufacturing Technology, 2009)
In recent years, the application of composite materials in aircraft and space vehicle structural components has become increasingly popular. Preventing failure of composite structural systems has been an important issue in engineering design. Due to the lack of through-the-thickness reinforcement, structures made from laminated composite materials and adhesively bonded joints are highly susceptible to failure caused by interfacial crack initiation and growth. The delamination phenomenon in a laminated composite structure may reduce the structural stiffness and strength and redistribute the load in a way that the structural failure is delayed or may lead to structural collapse. As the most application of these materials is in space structures, the failure of a composite structure component can lead to a catastrophic failure of the structure as whole, thus, an accurate quantitative measurement and understanding of damage and determination of remaining useful service life plays a vital role in prediction of failure of such structures. To do so, first, the fracture properties of material should be determined. To calculate these properties, there are several experimental methods. Among them, the modified Arcan test is one of the most apposite methods for in-plane mixed-mode loading condition. In this investigation, a new specimen has been introduced to reduce cost and problems concerning utilization of adhesively. The critical fracture parameters of carbon-epoxy woven laminated composite material, which is of paramount materials in industry, in room temperatures is calculated both with experimental and numerical methods. These parameters include the critical stress intensity factors and critical strain energy release rate on crack tip. The geometric correction factors for modified Arcan test are calculated with a 2D finite element analysis. Finally, the values of critical fracture properties are calculated using these geometric modification factors and critical loads generated via experimental procedure.